O gênero receita culinária no século XIX na perspectiva da historiografia linguística - Diniz, Raquel Cristina de Camilo (2013)
This study sought the extent to which socio-cultural and linguistic expressions, materialized in the genre cooking recipe, featuring the culture of Brazil in the XIX century. A cooking recipe acquires importance as it has always been linked to the limit socioeconomic-cultural-linguistic part of society, revealing thus the culture of the time intertwined with language and history. When we conduct a study historiographical linguistic, rescued, in context, the major historical events that have influenced the climate of opinion at the time recipe, in immanence, analyze revenues according to the grammarian of the period, and the theoretical adequacy, comparing recipes early XIX century with other current. Thus, the present study found that the cooking recipe of the XIX century have cultural elements characteristic of his time, as well as bring lexicon, syntax and spelling to grammar befitting your period